2013
DOI: 10.1109/lpt.2013.2281068
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Blue LEDs With Graded-Composition AlGaN/GaN Superlattice EBL

Abstract: InGaN/GaN light-emitting diodes (LEDs) with graded-composition AlGaN/GaN superlattice (SL) electron blocking layer (EBL) were designed and grown by metal-organic chemical vapor deposition. The simulation results demonstrated that the LED with a graded-composition AlGaN/GaN SL EBL have superior hole injection efficiency and lower electron leakage over the LED with a conventional AlGaN EBL or normal AlGaN/GaN SL EBL. Therefore, the efficiency droop can be alleviated to be ∼20% from maximum at an injection curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…[21][22][23] Although the graded SL-EBL and AlInGaN-based SL-EBL are proposed in DUV LEDs for optimization, the conventional AlGaN/AlGaN periodic SL-EBL may be preferred due to the lower growth complexity. [24][25] The design of the SL-EBL is usually dependent on the simulation software. The different combinations of composition and thickness are basic variables contributing to the various device capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Although the graded SL-EBL and AlInGaN-based SL-EBL are proposed in DUV LEDs for optimization, the conventional AlGaN/AlGaN periodic SL-EBL may be preferred due to the lower growth complexity. [24][25] The design of the SL-EBL is usually dependent on the simulation software. The different combinations of composition and thickness are basic variables contributing to the various device capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The p-type AlGaN/GaN heterojunction [18][19][20] and the AlGaN/GaN superlattice (SL) [21][22][23][24][25][26][27][28] have been reported to increase the hole concentrations of p-type GaN-based materials. Since then, similar concepts have been applied in many studies on GaN-based LEDs; such concepts include AlGaN/GaN/AlGaN quantum wells [29,30], AlGaN/GaN SLs [31], and graded AlGaN/GaN SLs [32,33]. Considering that the p-type AlGaN/GaN SL structure has presented promising results in GaN-based LEDs, a similar idea has been adopted to improve the hole concentration of high-Al content AlGaN in DUV LEDs [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Yin [17] investigated two types of AlGaN/GaN SL-EBL structures in GaN-based LEDs, and found that the SL-EBL with a step-graded Al molar fraction markedly decreased the efficiency droop. Lin et al [18] reported that the application of an AlGaN/GaN SL-EBL in GaN-based LEDs markedly enhanced the optical power output by as much as 60%. While the above-discussed studies have demonstrated the optimal Al-grading structure of these SL-EBLs, the mechanism remains unclear owing to a lack of systematic investigation.…”
Section: Introductionmentioning
confidence: 99%